Prevalence of body image dissatisfaction among males and females of Nishtar medical university, Multan - Tufail, Nadia; Saeed, Numrah; Salim, Taha; Sultana, Wusqa; Umer, Umair; Batool, Moazma; Sharif, Zamzama (International Journal Of Community Medicine And Public Health, 2025)
Background: Body image dissatisfaction is a widespread public health issue that is personified by a negative self-perception of one's physical appearance, frequently resulting from a disparity between one's ideal and perceived body composition. Research shows that young individuals in the South Asian region, including Pakistan, have a high prevalence of BID, especially in academic settings. Methods: This cross-sectional study was conducted on 316 students of Nishtar Medical University, Multan, to access knowledge and perception about body image dissatisfaction. The questionnaire developed includes maximum parameters/variables to access students’ perceptions about body image dissatisfaction. Results: The results of the examination of body image dissatisfaction (BID) among the 316 participants revealed that distinct body attributes were associated with varying degrees of satisfaction within the participants. This study identified 26 distinct elements that contribute to body image dissatisfaction. Particular issues included satisfaction with things like not looking slender (0.91) due to their mean score being below 0.96. According to the findings of the study, certain BID characteristics, such as having a distaste for the texture of the hair (1.30), and so on, have mean values that are greater than 0.96; it implies that they produce results for which they show dissatisfaction. Conclusions: BID refers to having unfavorable sentiments about one's own body. Body image dissatisfaction can be caused by a variety of circumstances. Mostly due to the fact that they are satisfied with their physical look and attributes.